Quetta Journey from Little London to Urban Crisis: https://doi.org/10.5281/zenodo.16942685 - Professor Dr Kaleem Ullah Barrech; Dr. Dost Barrech; Dr. Dawood Kakar (`, 2025)
Quetta, the capital of Balochistan was once called "Little London" on account of its scenic beauty, pleasant weather, and unique geographical location. The city currently has a population of 3.5 million confronts innumerable challenges. The capital is the only metropolitan city in the province but does not have all the features that a big city usually has. The flood of 2022 in the city further intensified the challenges. Much of the road, bridges, and railway tracks including the agriculture sector of Hanna Valley and Dasht of Spezand area till Kulpur washed away by the rains. The city has been facing the challenges of urban sprawl. There are many people with no or insufficient shelters in the city. The shortage or absence of water supply is a major challenge. More than 500 tube wells extract slightly above 20 million gallons per day, falling short of the demand that exceeds 30 MGD. The real estate business in the city is in full swing. Real estate projects have resulted in deforestation, insufficient groundwater for orchards, and the expansion of unplanned settlements, posing a threat to the local ecology. Quetta City requires efficient interventions to manage and plan population densities. This involves transforming transportation routes to enhance movement, managing commercial centers, and creating open public spaces. This paper, thus, will shed light on urbanization challenges in Quetta City and will provide concrete recommendations in a bid to modernize the city. Applied research will be used in the paper by using both primary and secondary data. Keywords: Population, Infrastructure, Metropolitan, Water Scarcity, Real Estate